A time-optimal algorithm for the estimation of contact distribution functions of random sets - Mayer, Johannes (Image analysis and stereology, 2004)
This paper presents a linear-time and therefore time-optimal algorithm for theestimation of distance distribution functions and contact distribution functions of random sets. The distance distribution function is the area fraction of a dilated set, where this function depends on the size of the structuring element used For the dilation. Furthermore, contact distribution functions arc related to distance distribution functions. Minussampling estimators are used for the estimation.
Keywords: Random Allocation; Slika, obdelava z računalnikom; Slučajnost, razporeditev; Sample Size; Vzorec, velikost; Image Processing, Computer-Assisted; porazdelitev delcev; algoritmi; kontakti